Dietary Habits of Saharawi Type II Diabetic Women Living in Algerian Refugee Camps: Relationship with Nutritional Status and Glycemic Profile - Alessandro Leone (Nutrients, 2020)
Diabetes is one of the main health problems among Saharawi refugees living in Algerian camps, especially for women. As is known, diet plays an important role in the management of diabetes. However, the dietary habits of Saharawi diabetic women are unknown. Therefore, we investigated the dietary habits and established their relationship with the nutritional status and glycemic profile of such women. We recruited 65 Saharawi type II diabetic women taking orally glucose-lowering drugs only. Dietary habits were investigated using qualitative 24 h recall carried out over three non-consecutive days. Anthropometric measurements were taken and blood parameters were measured. About 80% of the women were overweight and about three out of four women had uncompensated diabetes and were insulin resistant. The Saharawi diet was found to mainly include cereals, oils, sugars, vegetables (especially onions, tomatoes, and carrots), tea, and meat. Principal component analysis identified two major dietary patterns, the first one “healthy” and the second one “unhealthy”. Women in the higher tertile of adherence to the unhealthy dietary pattern had a higher homeostatic model assessment for insulin resistance (HOMA) index (b = 2.49; 95% CI: 0.41−4.57; p = 0.02) and circulating insulin (b = 4.52; 95% CI: 0.44−8.60; p = 0.03) than the women in the lowest tertile. Food policies should be oriented to improve the quality of diet of Saharawi diabetic women.